Severe rhabdomyolysis in homozygote carnitine palmitoyltransferase II deficiency - Schnedl, Wolfgang J.; Schenk, Michael; Enko, Dietmar; Mangge, Harald (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Carnitine palmitoyltransferase II (CPT II) deficiency represents an inherited defect in mitochondrial long-chain fatty acid oxidation. Rhabdomyolysis with necrosis of muscle is caused by the destruction of skeletal muscle and leads to systemic, multiorgan complications due to the release of intracellular muscle components. Severe rhabdomyolysis may be triggered by combination of a genetic predisposition, including CPT II deficiency, with additionally acting causes. Generally, patients with CPT II deficiency are rarely clinical recognized and reported. We describe a patient presenting severe rhabdomyolysis due to urosepsis, who, in genetic testing, demonstrated the homozygous CPT II deficiency (c.338C>T, p.Ser113Leu) mutation. The diagnosis of CPT II deficiency helped this patient to put the symptoms into context, and this reduced myopathy and the risk of recurring rhabdomyolysis. We report on this patient to increase awareness of diagnostic and medical management in CPT II deficiency.
EXCLI Journal;Vol. 19 2020
Keywords: Carnitine palmitoyltransferase II deficiency; Myalgia; Rhabdomyolysis; Urosepsis; 610